Health promoting behaviors and women knowledge about breast cancer prevention - Katarzyna Strojek; Małgorzata Maślanka; Hanna Styczyńska; Walery Zukow (Kazimierz Wielki University, 2017)
Introduction Breast cancer is one of the most often diagnosed malignant cancers in polish women. The most important role in reducing the mortality rate is early disease detection  and elimination of factors that increase the risk of developing breast cancer. Aim of the study The aim of the study was to evaluate the health promoting behaviors and the knowledge of breast cancer prevention in women. Materials and methods Study included 40 women who filled out a survey. Results In the study women gave 36% correct answers about breast cancer prevention. 30% of the surveyed women were educated by the television and 27% by the Internet.  90% of the surveyed women know how to  make self- examination of  their breasts, but only 35% of them do it regularly. Results The knowledge about breast cancer prevention is unsatisfactory in questioned women. There is a high need for better education about breast cancer and the healthy habits promotion.